Revitalization of Agarwood Planting in Forest Areas with the Specific Purpose of Senaru as an Income-Generating Investment for University of Mataram and Cultivators - Romdhini, Mamika Ujianita; Mulyaningsih, Tri; Muktasam, Muktasam; Baldovini, Nicolas; Takamatsu, Sakura; Nadia, Ahsanu; Puspita Dewi, Chandra (Universitas Ahmad Dahlan, 2025)
Background: Agarwood, valued for its aromatic fragrance, thrives in West Nusa Tenggara, where demand is very high. However, natural forest sources are scarce, driving up market prices and limiting supply. To address this, farmers have begun cultivating agarwood trees. Community service initiatives are urgent, as they offer economic, environmental, and social benefits. Contribution: This study introduces a community-based revitalization program for agarwood cultivation in the KHDTK (Forest Area with Specific Purpose) of Senaru. By integrating applied biotechnology with participatory forest management, the program provides empirical evidence of how agarwood planting can simultaneously improve rural livelihoods, support environmental rehabilitation, and contribute to broader debates in sustainable forestry and applied technology. Method: The methods include site assessment and sustainable land preparation, and staggered planting. A total of 2070 high-quality agarwood seedlings are distributed to local farmers, who received training in cultivation, maintenance, and resin production techniques. Monitoring was conducted over 6 months to evaluate survival, growth, and socio-economic outcomes. Results: After 6 months, 90% of seedlings survived, and carbon sequestration potential was estimated at 3.31 tons CO₂ per year. These findings indicate that agarwood revitalization can deliver measurable ecological and economic benefits. Conclusion: With proper implementation and support, this project can serve as a model for other regions seeking to balance ecological preservation with socio-economic growth.